DIAGNOSING CARDIAC AMYLOIDOSIS USING 99MTC-PYP AT DR. HASAN SADIKIN GENERAL HOSPITAL : First Case in Hasan Sadikin General Hospital - Iqbal Andi (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2022)
Amyloidosis is an infiltrative disease characterized by the deposition of abnormal fibril proteins in various tissues and organ systems, including the heart. Cardiac amyloidosis is a very rare disease. The diagnosis of amyloidosis is highly dependent on the suspicion of a clinician. This disease is often asymptomatic until eventually advanced which will give symptoms and symptoms can vary widely. As a result, the patient's diagnosis is often delayed. Cardiac ATTR amyloidosis can be diagnosed in the absence of histology in the setting of typical echocardiographic/CMR findings when 99mTc-PYP scintigraphy shows Grade 2 or 3 myocardial uptake of Radiotracer. Once cardiac ATTR amyloidosis is confirmed, genetic counselling and testing should be performed to assess for the presence of TTR mutations in order to differentiate between ATTRwt and ATTRv. Genetic testing should be performed even in elderly patients, as a significant number can have TTR mutations. 99mTc-PYP can differentiate between CA types and specific for ATTR types. Imaging modalities other than nuclear imaging, cannot differentiate the types of amyloidosis